A prospective, multi-centre, follow-up clinical study evaluating the safety and effectiveness of a 24mg/ml sodium hyaluronate soft tissue filler. (18th August 2021) - Kebede, Muna; Noah, Ernst Magnus; Weidmann, Michael; Choi, Soo Whan; Hofmann, Maja A.
ABSTRACT: Highly concentrated hyaluronic acid dermal fillers commonly contain 20 mg/ml sodium hyaluronate. The soft tissue filler SF 24 contains 24 mg/ml sodium hyaluronate. It is a viscoelastic gel, which is moderately cross-linked and specifically designed to correct moderate to deep wrinkles and folds of facial skin.To evaluate the long-term safety and effectiveness of the SF 24 for facial augmentation.The primary endpoints were effectiveness and safety, which were measured by investigators' assessment of wrinkle/ fold/ defect severity and reaction severity, respectively. The Global Esthetic Improvement Scale (GAIS) evaluated secondary endpoints, such as patient and physician satisfaction. Data collection occurred at treatment date (day 0) and at each visit set at an interval of 21 days, 121 days, 213 days, and 395 days. A total of 74 individuals (3 male and 71 female) received treatment with SF 24 across five sites. The baseline value (2. 70) of wrinkle and fold severity was reduced to 1.22 directly after treatment and remained improved even after 273 days at 1.59. The improvements compared to baseline were all significant (p < .001). The injection-related reactions were mainly short-term (1–7 days), mild to moderate in severity, and resolved without intervention. SF 24 is safe and effective for facial volume augmentation. It shows long-lasting (9 months) results in treated patients.